Could Hong Kong Primary Schoolchildren be Taught to Perform Compression-Only CPR: A Pilot Study. Issue 2 (March 2017) - Cy, CHAN; Ko, HF; Tsui, SY; Chan, OY; Tang, TH; Chu, YC
Objective: To evaluate whether Hong Kong primary schoolchildren could be taught to perform compression-only CPR. Design: Prospective experimental trial Subjects: Primary schoolchildren of age 9-12 years old from different Cub Scout packs attended a 2 hour voluntary compression-only CPR training session between late 2014 and mid-2015. Main outcome measures: Cardiopulmonary resuscitation (CPR) knowledge in the format of pre- and post-test multiple choices questions (MCQ). Psychomotor skills assessment including correct hand position, compression depth, compression rate and chest wall recoil between each compression. Results: A total of 112 primary schoolchildren attended the training session, in them 72% were boys. Pretest score and post-test score was 2.81/5 and 4.82/5, respectively. The difference was statistically significant (p<0.05). About 96% of subjects had correct hand position at all time during CPR. Mean compression rate was 119/minute. Mean compression depth was 3 cm. About 47% of subjects had 100% complete recoil of chest wall following compression. Conclusion: Primary schoolchildren above 9 years old are able to acquire essential knowledge and skills in compression-only CPR. Their physical strength may limit their ability to perform effective chest compression; it is still worthwhile to advocate CO-CPR education in primary schoolchildren in Hong Kong in order to raise their interest in this life saving skills and to equip them with essential cognitive skills in emergency situations. To achieve optimal cost-effectiveness and a compression depth of at least 4 cm, body weight of 53 kg or above should be considered as a selection criterion.